Teori Belajar Humanisme dalam Pembelajaran Berstandar Proses - Ridwan; Usman, Syahruddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
Humanistic learning theory positions human beings as the primary subjects in the learning process by emphasizing the holistic development of learners’ potential, encompassing cognitive, affective, and psychomotor aspects. This article aims to examine the concept of humanistic learning theory and its relevance to the implementation of learning based on educational process standards. This study employs a qualitative approach through a literature review of various relevant sources, including books, scholarly journals, and national education regulations. The findings indicate that humanistic learning theory, as proposed by figures such as Abraham Maslow and Carl Rogers, emphasizes the importance of self-actualization, freedom to learn, respect for individual uniqueness, and the creation of a safe, comfortable, and democratic learning environment. The application of humanistic theory within learning process standards is reflected in learner-oriented instructional planning, student-centered learning implementation, and assessment practices that focus not only on final outcomes but also on learners’ processes and development. Therefore, the integration of humanistic learning theory into process-standard-based instruction contributes to the formation of learners who are characterized by strong character, independence, reflectiveness, and the ability to optimally develop their potential in accordance with the demands of 21st-century education.